Practical Web Design : Learn the fundamentals of web design with HTML5, CSS3, Bootstrap, jQuery, and Vue.js. - Hong, Philippe (Packt Publishing, 2018)
Web design is the process of creating websites. It encompasses several different aspects, including webpage layout, content production, and graphic design. This book offers you everything you need to know for building your websites.